Note de conseils sur la plateforme numérique - Messa, Angele; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2025)
This document is a guidance note on digital platforms, specifically focusing on e-learning and the use of Opale and Moodle software. It aims to support the implementation of a digital learning platform in Madagascar. The report addresses questions and challenges faced by the Ministry of National Education in developing and deploying digital educational content. It covers various aspects of e-learning, including evaluation methods, content structuring, accessibility, interactivity, and technical requirements. Key topics include different evaluation models, types of e-learning evaluation (formative and summative), guidelines for using Opale, tablet specifications for online learning, ensuring course accessibility, and using Moodle both online and offline. The document also provides a checklist for ensuring quality in e-learning course development and implementation. Keywords: e-learning; Moodle; Opale; digital platform; accessibility; usability; Madagascar Ce document est une note d’orientation sur les plateformes numériques, avec un accent particulier sur l’e-learning et l’utilisation des logiciels Opale et Moodle. Il vise à soutenir la mise en place d’une plateforme d’apprentissage numérique à Madagascar. Le rapport aborde les questions et défis rencontrés par le Ministère de l’Éducation Nationale dans le développement et le déploiement de contenus éducatifs numériques. Il traite de divers aspects de l’e-learning, notamment les méthodes d’évaluation, la structuration des contenus, l’accessibilité, l’interactivité et les exigences techniques. Les principaux sujets incluent les différents modèles d’évaluation, les types d’évaluation en e-learning (formative et sommative), les recommandations pour l’utilisation d’Opale, les spécifications des tablettes pour l’apprentissage en ligne, l’accessibilité des cours et l’utilisation de Moodle en mode en ligne et hors ligne. Le document propose également une liste de contrôle pour garantir la qualité du développement et de la mise en œuvre des cours en e-learning. Mots clés: e-learning; Moodle; Opale; platforme numériques; accessibilité; usabilité; Madagascar An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen